Osteoporosis: disease severity and consequent fracture management. - Cooper, C (2010)
Osteoporosis is a systemic skeletal disease responsible for the high incidence of fractures in older subjects, particularly in postmenopausal women. The increasing prevalence with population ageing and prolonged life expectancy raises the rates of associated morbidity, loss of independence, and mortality. BMD and previous fracture history are two main risk factors associated with osteoporosis such that the presence of prior fractures can predict future fractures. Strontium ranelate is an agent developed for the management of postmenopausal osteoporosis, demonstrated to reduce vertebral, nonvertebral, major nonvertebral, and hip fractures. It has been demonstrated to be effective for a broad spectrum of patients, including women with osteopenia, osteoporosis, and severe disease.